1984
DOI: 10.1159/000299096
|View full text |Cite
|
Sign up to set email alerts
|

Relative Fatty Acid Composition of Lecithin during Postmenopausal Replacement Therapy – A Comparison between Ethinyl Estradiol and Estradiol Valerate

Abstract: The relative fatty acid composition of serum lecithin was followed in groups of women during postmenopausal replacement therapy. The effects of estradiol valerate and ethinyl estradiol in two different doses, and the modulating influence of various progestogens and antiestrogens were compared. Unopposed estrogen treatment enhanced liver lecithin synthesis along pathway I, i.e. reduced the amount of stearic acid and increased the amount of palmitic acid. The effect was clearly dose-dependent and even the low do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 3 publications
4
13
0
Order By: Relevance
“…The suggestion that oestrogen may increase the activity of the desaturation/elongation pathway is consistent with the finding that oestrogenbased hormone replacement therapy in postmenopausal resulted in greater plasma dihomo-γ-linolenic and arachidonic acid concentrations than before treatment [61]. Furthermore, DHA concentration in the plasma cholesteryl ester fraction has recently been shown to be greater in women (0.53% total fatty acids) compared to men (0.48% total fatty acids) consuming diets controlled for energy and αLNA content, although DHA is a minor component of this plasma lipid pool [62].…”
Section: The Effect Of Gender On α-Linolenic Acid Metabolismsupporting
confidence: 86%
“…The suggestion that oestrogen may increase the activity of the desaturation/elongation pathway is consistent with the finding that oestrogenbased hormone replacement therapy in postmenopausal resulted in greater plasma dihomo-γ-linolenic and arachidonic acid concentrations than before treatment [61]. Furthermore, DHA concentration in the plasma cholesteryl ester fraction has recently been shown to be greater in women (0.53% total fatty acids) compared to men (0.48% total fatty acids) consuming diets controlled for energy and αLNA content, although DHA is a minor component of this plasma lipid pool [62].…”
Section: The Effect Of Gender On α-Linolenic Acid Metabolismsupporting
confidence: 86%
“…On the other hand, in the HRT group, a few fatty acids of serum PL also changed, even though there were no significant changes in their fatty acid intakes. Several studies have suggested that estrogen can affect blood fatty acid composition, but we cannot conclude whether those changes are due to estrogen, or not (33,34). Even now, the effect of estrogen on serum fatty acid composition is controversial, and, as such, requires further research.…”
Section: Discussionmentioning
confidence: 83%
“…They suggest that the action of oestrogen may therefore explain greater synthesis of EPA and DHA from ALA in young women due to increased activity of the pathway. Ottosson et al reported that oestrogenbased hormone replacement therapy in postmenopausal women resulted in greater plasma di-homo-γ-linolenic and arachidonic acid (AA) concentrations than before treatment [178]. Giltay et al describe greater DHA concentrations in the plasma cholesteryl ester fraction of women (0.53% of total fatty acids) compared with men (0.48% of total fatty acids) after consumption of increased ALA [179].…”
Section: Sex Differences In Alpha-linolenic Acid Metabolismmentioning
confidence: 99%